The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/bmc.4368
|View full text |Cite
|
Sign up to set email alerts
|

Determination of glucosamine and monitoring of its mutarotation by hydrophilic interaction liquid chromatography with evaporative light scattering detector

Abstract: Saccharides and their derivatives are typical polar analytes without a suitable UV-chromophore that are nowadays analyzed by HPLC (high-performance liquid chromatography) under HILIC (hydrophilic interaction liquid chromatography) mode. Usually an evaporative light scattering detector (ELSD) is utilized which, however, gives a nonlinear response. A procedure to overcome the problem of mutarotating (time-varying) analytes recorded with such a nonlinear response detector is described. The procedure was applied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
(85 reference statements)
3
8
0
Order By: Relevance
“…As such, it was concluded that the two peaks corresponded to two anomeric forms of glucosamine. The ratio of the peak areas was calculated as 25.8/74.2 which was in good agreement with previously published results (38,39), meaning that the obtained peaks corresponded to the β-anomer (tR = 0.87 min) and α-anomer (tR = 1.03 min) of glucosamine, respectively. The incomplete baseline separation can be attributed to the interconversion between the two anomers through mutarotation, as reported previously (15,(38)(39)(40).…”
Section: Chromatographic Conditionssupporting
confidence: 91%
See 1 more Smart Citation
“…As such, it was concluded that the two peaks corresponded to two anomeric forms of glucosamine. The ratio of the peak areas was calculated as 25.8/74.2 which was in good agreement with previously published results (38,39), meaning that the obtained peaks corresponded to the β-anomer (tR = 0.87 min) and α-anomer (tR = 1.03 min) of glucosamine, respectively. The incomplete baseline separation can be attributed to the interconversion between the two anomers through mutarotation, as reported previously (15,(38)(39)(40).…”
Section: Chromatographic Conditionssupporting
confidence: 91%
“…The ratio of the peak areas was calculated as 25.8/74.2 which was in good agreement with previously published results (38,39), meaning that the obtained peaks corresponded to the β-anomer (tR = 0.87 min) and α-anomer (tR = 1.03 min) of glucosamine, respectively. The incomplete baseline separation can be attributed to the interconversion between the two anomers through mutarotation, as reported previously (15,(38)(39)(40). For calibration and quantification, both peaks as well as the plateau were integrated and the total area was used.…”
Section: Chromatographic Conditionssupporting
confidence: 91%
“…Initial experimental conditions for the method optimization were based on recently published papers on study of monosaccharides and disaccharides retention on a polyol stationary phase [ 25 , 26 , 27 , 55 ], where a diol column (Lichrosphere100 DIOL, Merck, Darmstadt, Germany) [ 25 , 26 ] was mostly applied, but in this paper we used a HALO PentaHILIC column that showed a better performance [ 27 ]. Due to the high affinity towards the stationary phase, a flow rate of 2.0 mL/min could be maintained in all experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a compromise between high retention (high resolution) and sufficient peak area must be chosen. To find better experimental conditions we followed our own experience [ 27 , 55 ]; in the following experiments several ammonium buffers (formate, acetate, bicarbonate) in a mixture with acetonitrile were tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation